Penyelarasan Strategi Bisnis dan Teknologi Informasi yang Efektif dengan Metode Balanced Scorecard Pada PT XYZ - Suryani, Eli; Fadli, Muhammad (Bina Nusantara University, 2011)
Along with the dynamic changes in business environment, information technology strategy map becomes an effective and flexible mechanism to visualize critical strategic actions required for the company and information technology (IT) organization to achieve its objectives. On the other hand, IT is perceived as a center of cost and investment. Therefore, IT benefit values become very important to measure and communicate. Using Balanced Scorecard method, this study aims to design IT strategy map aligned with the corporate strategy and effective measurement of IT performance in its contribution to achieve corporate objectives. The method is designed based on the results of data and information analysis gathered from executive interviews, focus group discussions and workshops at the company. Balanced Scorecard is a comprehensive and effective tools to measure, monitor and evaluate the performance of IT critical success factors (CSFs) to support the corporate objectives.